Early-Onset Sensorineural Hearing Loss in a Child with Turner Syndrome - Roush, Jackson; Davenport, Marsha L.; Carlson-Smith, Connie (Journal of the American Academy of Audiology, 2000)
Turner syndrome is among the more common but less familiar syndromes that include sensorineural hearing loss and middle ear disease. This article provides a review of the syndrome, an illustrative case, and a review of specific issues relevant to audiologic management of patients with Turner syndrome.Abbreviations: GH = growth hormone, TS = Turner syndrome
Keywords: Conductive hearing loss; sensorineural hearing loss; Turner syndrome